Experimental Investigation on the Average Surface Roughness (Ra) of AlSi10Mg Alloy Manufactured by Laser Powder Bed Fusion Method. (7th July 2022) - Refaai, Mohamad Reda A.; Prakash, D.; K G, Jaya Christiyan; Prasad, DVSSSV; Archana, E.; Shata, Agegnehu Shara
Abstract : AlSi10Mg alloy is an extensively utilised material having good mechanical qualities. The laser powder bed fusion procedure has been applied for fabricating the aluminium alloy (AlSi10Mg) plates in this research. Different exposure periods and scan techniques were applied in this work to measure the average roughness. Results demonstrate that the energy density grew and roughness reduced at first and then improved. Furthermore, there were considerable differences in roughness throughout the created faces. At 125 J/mm 3 and 180 J/mm 3, excellent surface quality was attained. By this experiment, it was noticed that the direction of scan, wiper movement, and gas flow are the key parameters.